SCHOOL PROTECTION SYSTEM: PROTECTING WHO, FROM WHOM? - Scotuzzi, C. A. S. [UNESP]; Adam, J. M. [UNESP] (Elsevier B.V., 2012)
The main objective of this article is to analyze the policy implanted in the schools in the State of São Paulo, Brazil, with a view to the prevention and intervention in the violence that occurs in the schools. The importance of such discussion is related to the analysis of the principles that are present and of the possible effectiveness of such a program in the school violence. This research is qualitative and the research methodology used was documentary analysis. The documents analyzed were those related to the policy of preventing violence in schools in the state of São Paulo/Brazil, called Protection System School. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The Association of Science, Education and Technology
Keywords: school violence; educational policy; prevention policy in schools